Atomic Processes in Plasmas and Gases - Oks, Eugene (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Atomic processes in plasmas and gases encompass broad areas in theoretical, experimental, atomic and molecular physics. One example is atomic processes that are involved in the study of various plasmas over a wide range of electron densities and temperatures. The topics in this area covered in the present book include magnetic fusion plasmas, laser-produced plasmas, as well as plasma spectroscopy for all of the above applications. Another example is atomic and molecular processes in neutral gases. Rydberg polar molecules in particular are covered in this book.